Sequential responsive nano-PROTACs for precise intracellular delivery and enhanced degradation efficacy in colorectal cancer therapy - Liuqing Yang; Ye Yang; Jing Zhang; Minghui Li; Long Yang; Xing Wang; Meifang Chen; Hua Zhang; Bing He; Xueqing Wang; Wenbing Dai; Yiguang Wang; et al. (Signal Transduction and Targeted Therapy, 2024)
Abstract PROteolysis TArgeting Chimeras (PROTACs) have been considered the next blockbuster therapies. However, due to their inherent limitations, the efficacy of PROTACs is frequently impaired by limited tissue penetration and particularly insufficient cellular internalization into their action sites. Herein, based on the ultra-pH-sensitive and enzyme-sensitive nanotechnology, a type of polymer PROTAC conjugated and pH/cathepsin B sequential responsive nanoparticles (PSRNs) are deliberately designed, following the construction of the PROTAC for Cyclin-dependent kinase 4 and 6 (CDK4/6). Colorectal cancer (CRC) which hardly responds to many treatments even immune checkpoint blockades was selected as the tumor model in this study. As a result, PSRNs were found to maintain nanostructure (40 nm) in circulation and efficiently accumulated in tumors via enhanced permeation and retention effect. Then, they were dissociated into unimers (<10 nm) in response to an acidic tumor microenvironment, facilitating tumor penetration and cellular internalization. Eventually, the CDK4/6 degrading PROTACs were released intracellularly following the cleavage of cathepsin B. Importantly, PSRNs led to the enhanced degradation of target protein in vitro and in vivo. The degradation of CDK4/6 also augmented the efficacy of immune checkpoint blockades, through the upregulation of programmed cell death-ligand 1 (PD-L1) expression in cancer cells and the suppression of regulatory T cells cell proliferation in tumor microenvironment. By combination with α-PD-1, an enhanced anti-tumor outcome is well achieved in CT26 tumor model. Overall, our study verifies the significance of precise intracellular delivery of PROTACs and introduces a promising therapeutic strategy for the targeted combination treatment of CRC.